2015
DOI: 10.1515/prolas-2015-0026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Application Rate and Meteorological Conditions on β-Glucan Content in Naked and Husked Oat Grain

Abstract: The objective of this study was to determine the effect of applied nitrogen fertilizer rate on β-glucan content in oat (Avena sativa L.) grains. The study was carried out at the State Stende Cereal Breeding Institute from 2011 to 2014. Three nitrogen surface fertiliser treatments (80, 120 and 160 kg·ha-1) were applied on one husked oat (variety 'Lizete') and two naked oat genotypes (breeding lines 'S-156' and '33793'). The content of β-glucan in naked oat genotypes was significantly (p < 0.05) higher than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The prerequisite for the production of high quality foodstuffs is a high quality raw material -grain. The results of studies on oats in Latvia confirmed that grain quality indices can be affected by the weather conditions during the growing season, location and genotypes (Bleidere et al, 2012), meteorological conditions (Zute et al, 2010) and nitrogen management (Brunava et al, 2015). Therefore development of oat cultivars adaptable to changing climatic conditions and capable of ensuring both stable yields and corresponding grain quality from year to year is the most significant task for oat breeders in Latvia.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The prerequisite for the production of high quality foodstuffs is a high quality raw material -grain. The results of studies on oats in Latvia confirmed that grain quality indices can be affected by the weather conditions during the growing season, location and genotypes (Bleidere et al, 2012), meteorological conditions (Zute et al, 2010) and nitrogen management (Brunava et al, 2015). Therefore development of oat cultivars adaptable to changing climatic conditions and capable of ensuring both stable yields and corresponding grain quality from year to year is the most significant task for oat breeders in Latvia.…”
Section: Introductionmentioning
confidence: 85%
“…'Stendes Emilija', included in this study, is the first local naked oat cultivar registered in Latvia. Other studies showed that grains of naked cultivars have an excellent biochemical composition -high levels of soluble fibres such as betaglucan (Brunava et al, 2015), crude protein (Sterna et al, 2016) and high content of α-tocopherol (Sterna et al, 2014) -traits, determining dietary quality of products.…”
Section: Introductionmentioning
confidence: 99%